Penatalaksanaan Perawatan Saluran Akar pada Gigi dengan Lesi Abfraksi : Laporan Kasus - Reni Nofika; Annisa Fajriatul Arafah (Faculty of Dentistry Universitas Andalas, 2021)
Background: Pulp and periapical disease may also result from the presence of a cervical cavity reaching the pulp chamber as an abfraction lesion. Abfraction causes the dentinal tubules to be exposed so that it becomes a pathway for microorganisms to enter the pulp. Root canal treatment in cases with abfraction lesions requires special management, so that contamination does not occur during treatment due to the exposed cervical part. Objective: Discusses the management of root canal treatment in teeth with abfractional lesions that penetrate the pulp chamber. Case Management: A 53-year-old male patient came RSGM Unand because he wanted to be treated for a cavity in his right lower posterior tooth and had a sudden throbbing pain. Based on the results of subjective, objective and preoperative radiographs, tooth 45 was diagnosed with pulp necrosis with chronic apical abscess. Pulp and periapical disease of tooth 45 was probably caused by the entry of microorganisms through the abfraction lesion that reached the pulp chamber. Temporary coronal seal of the abfraction cavity and access occlusal cavity is necessary to prevent the entry of microorganisms during root canal treatment procedures. The final restoration is a direct composite resin using a fiber-reinforced composite (FRC). Conclusion: The management of root canal treatment in this case of abfraction lesion showed success as indicated by the absence of subjective complaints, objective examination showed negative results, and periapical lesions showed healing seen on periapical radiographs.